2006
DOI: 10.1016/j.visres.2006.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Color discrimination in carriers of color deficiency

Abstract: Carriers of X-linked color vision deficiencies have previously been reported to exhibit mild abnormalities of color matching and discrimination. In a sample of 55 carriers of protan and deutan deficiencies and 55 age-matched normal controls, we measured chromatic discrimination along a red-green axis. We found that discrimination was impaired in the case of carriers of deutan deficiencies (which affect the middle-wave-sensitive cones of the retina), but was normal in the case of carriers of protan deficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 34 publications
2
38
2
Order By: Relevance
“…However, this general assumption is not supported by findings from Hood et al's (2006) study that showed some heterozygote females (i.e., carriers for deutan defects), but not others (i.e., carriers for protan defects) have poorer RG colour discrimination when compared with homozygotes. We, therefore, applied two different analyses: one which controlled for the possible influence of carriers of deutan defects and a second which controlled for the possible influence of carriers of either defect.…”
Section: -Test)mentioning
confidence: 86%
See 1 more Smart Citation
“…However, this general assumption is not supported by findings from Hood et al's (2006) study that showed some heterozygote females (i.e., carriers for deutan defects), but not others (i.e., carriers for protan defects) have poorer RG colour discrimination when compared with homozygotes. We, therefore, applied two different analyses: one which controlled for the possible influence of carriers of deutan defects and a second which controlled for the possible influence of carriers of either defect.…”
Section: -Test)mentioning
confidence: 86%
“…Why should this be the case? Hood et al (2006) have offered one explanation for why deutan carriers may have slightly impaired red-green colour discrimination compared with males. They speculate these differences can be explained by differences in the relative numbers of L-and M-cones in heterozygous retinae.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] As far as color normal persons of both genders are concerned, vision science literature stated that differences between color normal men and women in red-green color discrimination were not significant if color deficient males and females and heterozygote female carriers (15%) were excluded from comparisons. 11 When color assessment and diagnosis test was performed on 150 color normal males and the same number of color normal females, no significant gender-related difference was recorded. 12 Several dentistry-related studies offered evidence on nonsignificance of differences in shade matching results between color normal females and males.…”
Section: Introductionmentioning
confidence: 95%
“…Some carriers may also exhibit a shift in Nagel match midpoint (MMP) and an enlarged Nagel matching range (MR) when tested by Rayleigh anomaloscopy [2,[6][7][8][9]. Protan carriers are less sensitive to red light, a characteristic known as Schmidt's sign [6,[10][11][12]. Deutan carriers, on the other hand, are more sensitive to red light [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%